Introducing English vocabulary to young learners with flashcards - Eka Amaranggana Ahmadi Suryani; A. Halim Majid; Suryani Suryani (Universitas Syiah Kuala, 2022)
English has become the most commonly spoken language in the modern era. English should be taught in every primary school because it is widely used. The most important skill to master when studying the English language is vocabulary. Hence, before learning any language skill, such as reading, writing, or listening, students must first learn vocabulary. Flashcards are a visually appealing medium that can help students understand vocabulary. This study aimed to improve the vocabulary of sixth-grade pupils at an elementary school in Lam Awee, Aceh Besar, using flashcards. The sample was taken from the sixth grade which consisted of 6 students. The data was collected using a vocabulary matching test consisting of questions covering parts of body, family, color, and fruit. The data were analyzed by testing the hypothesis at the significance level of 0.05. The results showed that the student vocabulary score improved significantly after learning the language using flashcards. Therefore, it is recommended for teachers to use flashcards to provide a basic vocabulary to beginners because it helps boost students’ motivation to learn new English vocabulary.